Glacial Lake Pickering: stratigraphy and chronology of a proglacial lake dammed by the North Sea Lobe of the British–Irish Ice Sheet. (15th January 2016) - Evans, David J. A.; Bateman, Mark D.; Roberts, David H.; Medialdea, Alicia; Hayes, Laura; Duller, Geoff A. T.; Fabel, Derek; Clark, Chris D.
ABSTRACT: We report the first chronology, using four new optically stimulated luminescence dates, on the sedimentary record of Glacial Lake Pickering, dammed by the North Sea Lobe of the British–Irish Ice Sheet during the Dimlington Stadial (24–11 ka cal BP). Dates range from 17.6 ± 1.0 to 15.8 ± 0.9 ka for the sedimentation of the Sherburn Sands at East Heslerton, which were formed by multiple coalescing alluvial fans prograding into the falling water levels of the lake and fed by progressively larger volumes of debris from the Wolds. Fan formation ceased ∼15.8 ka, at a time when permafrost was degrading and nival‐fed streams were no longer capable of supplying sediment to the fans. A further age of 10.1 ± 0.7 ka dates the reworking of coversand into the early part of the Holocene, immediately post‐dating Younger Dryas periglacial structures. A 45‐m lake level dates to ∼17.6 ka, when the North Sea Lobe was already in retreat, having moved eastward of the Wykeham Moraine; it stood further east at the Flamborough Moraine by ∼17.3 ka. The highest (70 m) lake level and the occupation of the Wykeham Moraine date to an earlier phase of the North Sea Lobe occupation of the Vale of Pickering.